Cognitive teaching methods in the process of studying pharmaceutical management and marketing - N. O. Tkachenko; V. O. Demchenko; E. G. Knysh (Zaporozhye State Medical University, 2014)
Some cognitive methods (method of empathy, the method of the symbolic vision, method comparisons, the method of the facts, research method, the method of error prediction method) have been considered in the article, and the problems and peculiarities of their use in the study of pharmaceutical management and marketing have been identified.